PENGARUH VARIASI KONSENTRASI CROSCARMELLOSE SODIUM SEBAGAI SUPERDISINTEGRANT TERHADAP KARAKTERISTIK FISIK FAST DISSOLVING TABLET (FDT) GLIBENKLAMID - Sendy Fitriani; Monica Kristiani (Journal Clinical Pharmacy and Pharmaceutical Science, 2022)
Glibenclamide is a second generation DM drug sulfonylurea group with the properties of lowering blood sugar levels. Most glibenklamid preparations are available in conventional tablet form and can be developed into pharmaceutical preparations that are more practical and accelerate the therapeutic effect of Fast Dissolving Tablet (FDT). The physical characteristics of the FDT are faster wetting and disintegration times compared to conventional tablets. Superdisintegrant is an important component in FDT preparations because it affects the time of wettability and disintegration time of FDT. The purpose of this study was to determine the effect of variations in the concentration of croscarmellose sodium as a superdisintegrant on the physical characteristics of FDT glibenclamide preparations of croscarmellose sodium concentration which gave the best characteristics.The type of research used is experimental research. Used study design a completely randomized pattern design in line with one factor. The manufacture of glibenclamide FDT uses the direct press method. The croscarmellose sodium concentration used is 3%, 4%, and 5%. The testing of FDT physical characteristics includes organoleptic, uniformity of weight, dimensions, hardness, friability, wettability time and FDT disintegration time.The results of statistical analysis showed that variations in the concentration of croscarmellose sodium as a superdisintegrant had an effect on the physical characteristics of FDT glibenclamide which included hardness, wettability and disintegration time, but had no effect on organoleptic, uniform weight, dimensions, and fragility. Based on the results of the characteristics and statistics, the formula III is the formula that provides the best physical characteristics.